INSTITUTIONAL STUDY OF SINGLE-STAGE LOCOREGIONAL FLAP FOR UPPER LIMB SOFT TISSUE DEFECT - MOHANTY, SATYABRATA; GUPTA, JITENDRA KUMAR (International Journal of Current Pharmaceutical Research, 2023)
Objective: Traumatic injuries involving the upper limbs present complex challenges, necessitating effective soft tissue coverage for optimal outcomes. This manuscript explores soft tissue reconstruction techniques for upper limb trauma, focusing on insights from a study conducted in Jaipur, India. The study evaluates the use of locoregional pedicled flaps and abdominal pedicled flaps in this specific context. Methods: A study involving 50 patients was conducted to assess outcomes of locoregional and abdominal pedicled flaps for upper limb soft tissue defects. Patient profiles, surgical procedures, and outcomes were analyzed. Locoregionalpedicled flaps included the Posterior Interosseous Artery Flap (PIAF) and the Reverse Radial Forearm Flap (RRFF), while abdominal pedicled flaps employed the Superficial Circumflex Iliac Artery (SCIA) flap and Superficial External Pudendal Artery (SEPA) flap. Results: Locoregionalpedicled flaps exhibited favorable outcomes, with efficient defect coverage and rapid mobilization, leading to improved joint mobility and function. Abdominal pedicled flaps achieved coverage but with longer immobilization periods and limited joint mobility. Comparative analysis indicated superior results with locoregional flaps in terms of functional restoration, patient satisfaction, and early mobilization. Conclusion: This study highlights the efficacy of locoregional pedicled flaps for upper limb soft tissue reconstruction in Jaipur. The advantages of rapid mobilization and improved functional outcomes make locoregional flaps preferable. Abdominal pedicled flaps offer coverage but are associated with challenges in joint mobility due to prolonged immobilization. Tailoring flap techniques to patient and regional factors optimizes outcomes in upper limb soft tissue reconstruction.